2015
DOI: 10.1186/s13054-015-0911-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum substance P levels are associated with severity and mortality in patients with severe traumatic brain injury

Abstract: IntroductionSubstance P (SP) is a member of the tachykinin family of neuropeptides, which are widely distributed throughout the central nervous system (CNS) and actively involved in inflammatory processes. SP is released early following acute injury to the CNS, promoting a neurogenic inflammatory response characterized by an increase in the permeability of the blood–brain barrier and the development of vasogenic edema. High levels of SP could lead to an exacerbated inflammatory response that could be fatal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 60 publications
5
26
0
Order By: Relevance
“…In a study by our team (to our knowledge, the first study to include data on serum SP levels in patients with severe TBI) was found that non surviving TBI patients showed higher serum SP levels than survivors (420 (310 - 815) vs. 250 (99 - 496); P = 0.002), and that serum SP levels were associated with TBI severity and with early mortality ( 24 ). We found that the area under the curve (AUC) for serum SP levels as a predictor of 30-day mortality was 0.70 (95% CI = 0.60-0.79; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by our team (to our knowledge, the first study to include data on serum SP levels in patients with severe TBI) was found that non surviving TBI patients showed higher serum SP levels than survivors (420 (310 - 815) vs. 250 (99 - 496); P = 0.002), and that serum SP levels were associated with TBI severity and with early mortality ( 24 ). We found that the area under the curve (AUC) for serum SP levels as a predictor of 30-day mortality was 0.70 (95% CI = 0.60-0.79; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Substances P plays role in inflammation through astrocyte and leukocyte activation at the site of injury (Lorente et al, 2015). A number of enzymes are required in the metabolism of substances P, including: neutral endopeptidase (NEP), angiotensin-converting enzyme (ACE), substance-P-degrading enzyme, cathepsin-D and cathepsin-E.…”
Section: Discussionmentioning
confidence: 99%
“…High SP levels in the serum of patients with severe TBI have reportedly correlated with increased mortality (Lorente et al, 2015). Elevated SP serum levels have also been reported in patients with major depression, levels that decline in responders treated with antidepressant (Bondy et al, 2003).…”
Section: Paper Iv: Sex-specific Differences In the Monoamine Systems mentioning
confidence: 98%